(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The aim of this study is to analyses the relationship of self confidence anxiety with actualisation and non actualisation of general mental ability of secondary school students. This is a descriptive-analytic study which was conducted on high school students who were 16-18 years old, in two schools. Data collection was done by applying emographic information questionnaire and Coppersmith Self-Esteem scale. The relationship between age, parental age, economic status self confidence and anxiety was assessed. Finally, data were analyzed by in SPSS software, using correlation test and ANOVA. Data analysis reported Girls (M = 50.331) are found to be slightly more intelligent than boys (M= 49.669). Rural high school students are more anxious (M= 52.068) than urban high school students (M= 47.931).